IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI KOTA PALU (STUDI PENGELOLAAN SAMPAH DI KELURAHAN TONDO) - Afandi Afandi; Nasir Mangngasing; Nuraisyah Nuraisyah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Afandi. B10222053. Thesis Title: Implementation of Waste Management Policy in Palu City (Study of Waste Management in Tondo Village). Mentors Nasir Mangngasing and Nuraisyah.This research is to determine the implementation of waste management policies in Palu City (Study of Waste Management in Tondo Village). The type of research used is descriptive qualitative. Data types use primary data and secondary data. Data collection techniques are carried out through observation, interviews and documentation. The informant withdrawal technique uses purposive. The data analysis used is the Miles, Huberman and Saldana model, namely data collection, data presentation, data condensation and drawing conclusions. The waste problem in Tondo Village is basically the responsibility of all parties, including the community, companies and local government. The habit of people who like to throw rubbish out of place makes waste management in this area increasingly ineffective and difficult to overcome. This habit of throwing rubbish carelessly is caused by a lack of education and facilities at rubbish dumps and final disposal sites. In fact, the current increase in population in Tondo Village will have an impact on the balance of the city, including waste production. The greater the population of an area, the more waste produced every day will also increase. Based on the results of research conducted, the implementation of the Waste Management Policy in Tondo Village is relatively ineffective, there are still many problems that need to be resolved so that waste handling can be more optimal, starting from aspects, human resources, budget resources and equipment resources. Apart from that, the disposition aspect related to sanctions and fines is relatively inconsistent in its implementation. The bureaucratic structure related to standard operational procedures in implementing policies, all of which have different problems from one another, so that commitment from the government and the community is needed to manage waste together.